2016
DOI: 10.1161/jaha.116.004198
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Effect of Isolated Nocturnal Hypertension in Chinese Patients With Nondialysis Chronic Kidney Disease

Abstract: BackgroundIsolated nocturnal hypertension (INH) has been studied among the general population and hypertensive patients. However, little insight is available on the prognostic effect of INH in patients with chronic kidney disease (CKD). This study investigated the prognostic effect of INH in a cohort of Chinese patients with nondialysis CKD.Methods and ResultsA total of 588 Chinese CKD patients who were admitted to the Third Affiliated Hospital of Sun Yat‐Sen University were enrolled in this study. We monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 26 publications
2
25
0
1
Order By: Relevance
“…Kario et al showed that nocturnal systolic BP, measured by home BP monitoring, was associated with urinary albumin/creatinine ratio, LV mass index, brachial-ankle 42 Presta et al showed that patients with masked hypertension and reverse BP pattern had a significantly higher risk of stroke, even after adjustment for age, gender, BMI, dyslipidemia, and diabetes. 43 Even though reverse dipping pattern does not always mean nocturnal hypertension, in this study the patients with reverse dipping also had nocturnal hypertension.…”
Section: Target Organ Damagementioning
confidence: 99%
“…Kario et al showed that nocturnal systolic BP, measured by home BP monitoring, was associated with urinary albumin/creatinine ratio, LV mass index, brachial-ankle 42 Presta et al showed that patients with masked hypertension and reverse BP pattern had a significantly higher risk of stroke, even after adjustment for age, gender, BMI, dyslipidemia, and diabetes. 43 Even though reverse dipping pattern does not always mean nocturnal hypertension, in this study the patients with reverse dipping also had nocturnal hypertension.…”
Section: Target Organ Damagementioning
confidence: 99%
“…The cuff was matched to the perimeter of the arm, and measurements of BP and PR were performed every 15 minutes in the daytime and every 30 minutes at night. Patients underwent 24‐hour ABPM using the TM‐2430 Monitor as previously reported . Before beginning ABPM, BP was measured according to standardized protocols, which has also been reported previously .…”
Section: Methodsmentioning
confidence: 99%
“…Patients underwent 24‐hour ABPM using the TM‐2430 Monitor as previously reported . Before beginning ABPM, BP was measured according to standardized protocols, which has also been reported previously . All patients underwent standard supine 12‐lead electrocardiogram detection after the individual had rested in the supine position for 5 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Ambulatory blood pressure monitoring (ABPM) could provide detailed information on BP over a 24h period, and it is unanimously recommended by guidelines for BP management 5-6[ii] 7 . Previously, we have reported the high prevalence and prognostic value of nighttime hypertension in CKD patients compared with clinic blood pressure [8][9] [iii] 10 . Recent evidence from large-scale cohort study also suggests that higher 24-hour and nighttime blood pressure measurements were signi cantly associated with greater risks of death and cardiovascular disease, even after adjusting for other o ce-based or ambulatory blood pressure measurements 11 .…”
Section: Introductionmentioning
confidence: 99%